ศีลกับการบรรลุนิพพานในพระพุทธศาสนาเถรวาท - ธันย์ธนัช ศรีนวลไชย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of the study is to analyze Sīla and Attainment of Nibbāna in Theravāda Buddhism, and to analyze the relationship between Sīla and Attainment of Nibbāna. From the study, It was found that Sīla that can take practitioner to attain Nibbāna must be pure Sīla, such as concluding version of the Sīla, given by monks to laypersons, that “ Sīlana Nibbutim Yanti ”. The version has no clear historically record and not found in Tripitaka, it added later by next generation. This kind of Sīla can lead the one to attain Nibbāna and to escape from sufferings. Sīla is the primary, the leader, and is the source of all virtues. Sīla has many levels, from rough to delicate, by which the practitioners can rely on to Nibbāna. It is true that only Sīla cannot lead anyone to Nibbāna. One need to observes Sīla, along with practice Concentration and Wisdom, along the Noble Eightfold path, making them a union one, this only can be dynamic power to Nibbāna. Therefore, Sīla is a necessary condition to attain Nibbāna. Sīla is the intention to avoid or rules to control the conduct expressed in physical, verbal action. Sīla is positive factor to prevent our mind from falling to evil condition, by which our mind can be clear, calm and pure. With Sīla as a condition, Concentration rises and with the concentration as a condition, Wisdom arises. Ignorance, passion and desire was eradicated, in the level of wisdom. In this level, people are of purity and deliverance. Therefore, the good actions rooted in Sīla, are benefit in cultivation of high quality of mind. The more advanced in practice, the more importance of Sīla will be given. As a saying of the Buddha “One should observe Sīla unto life, Sīla will protect us from falling woe. Sīla will lead us to the highest aim that is, Nibbāna.”